Hubungan antara Cyber Public Relations dalam Mengkomunikasikan Etika Bisnis dan Citra Burgreens - Dwijayanti, Jovita; KusumastutiYatri Indah (Jurnal Komunikasi Pembangunan, 2018)
Now days, internet users had spread like a wildfire. Cyber Public Relation, as one of Public Relation’s activity to fulfill the external’s need of information. Fulfilling the external’s need of information about the enterprise’s business ethic is very useful in forming a positive image on the public’s eyes. The aim of this research is to analyze the relationships between communicating business’ ethic through cyber public relations on Burgreens’ Image. This research uses an accidental sampling method. People who is 25 years or above, who is active on cyber space, and who is considered have an awareness of the importance of healthy life, is the unit analysis of this research. The results shows that the implementation of cyber PR in communicating Burgreens’ business ethic could create a positif image.